'Without decontextualisation': the Stanley Royd Museum and the progressive history of mental health care. Issue 3 (September 2015) - Ellis, Rob
This paper builds on recent scholarship exploring museum exhibitions and the heritage of mental health care. Using the development of the Stanley Royd Museum in the mid-1970s as a case study, the paper will examine the rationale for the opening of the museum and its link to changing perceptions of mental hospitals in both historical study and what was then 'current' practice. It will then provide an overview of the proposed audience for the new museum and briefly analyse its success in communicating its history to its visitors. Ultimately, it will question how successful mental health professionals were in presenting the progressive nature of institutional care at a time when the system was being radically overhauled and reoriented.